'I don't feel trapped anymore…I feel like a bird': People with Learning Disabilities' Experience of Psychological Therapy. Issue 5 (29th June 2015) - Lewis, Nicola; Lewis, Karin; Davies, Bronwen
Abstract : Background: There are very few studies that investigate the qualitative experiences of people with a learning disability who have engaged in psychological therapy. Indeed, having a learning disability has traditionally been an exclusion criterion for good quality research about psychological treatments ( Psychotherapy and Learning Disability. Council Report CR116 . London: Royal College of Psychiatrists, 2004; Journal of Applied Research in Intellectual Disabilities, 19, 2005 and 5). The current research was developed in response to a clinical psychology service recognizing the need to evaluate their psychological service and, as part of this evaluation, the importance of consulting with service users about their experience of psychological therapies. The overall aim of gaining this feedback would be to improve the service offered and to ensure that people receive the best psychological care. Methods: Six service users with a learning disability were interviewed about their experience of individual psychological therapy. The interviews were analysed using interpretative phenomenological analysis. Results: Themes were generated from the interviews which highlighted both positive and negative feedback on the psychological therapy process. The feedback covered areas such as access to therapy, feelings about therapy, preparing for therapy, skill development and collaborative working, accessibility and making therapy fun, challenges to confidentiality, positive feelings towards the therapist, aspects of the therapeutic relationship, therapy being challenging but helpful, and positive outcomes. Conclusions: These results have contributed to the evidence base that people with a learning disability are able to meaningfully engage in research and provide essential feedback on the services that they receive. No longer can people be excluded from individual psychological therapy or research just because of their label.